Student’s Response to the Google Classroom Application in Learning English of Junior High School Students: Tanggapan Siswa terhadap Aplikasi Google Classroom dalam Pembelajaran Bahasa Inggris Siswa Sekolah Menengah Pertama - Anggreani, Vinna; Mandarani, Vidya (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine student responses to the use of the google classroom application in online learning of English subjects for class VIII-C SMPN 1 Prambon. Therefore, to support the smooth process of learning activities during the pandemic, teachers are emphasized to be more creative and innovative so that learning activities remain effective even though they are carried out online. As part of supporting the teaching and learning process, teachers use online learning application media. The online learning application media currently used by teachers at SMPN 1 Prambon is the Google Classroom application media. By using the google classroom application media, teachers can share materials and assignments for students while students can access materials and assignments that have been shared by the teacher and can be done in the application provided by the teacher. In this study used descriptive qualitative research methods by conducting direct interviews. The research location is at SMPN 1 Prambon. The results of student responses to the use of the Google Classroom application in online English learning have positive and negative responses. There are benefits that are felt by students, namely saving time, being easy and practical in carrying out learning process activities and being considered effective in the current pandemic conditions. In learning English, students are more interested in paying attention to the material provided in the form of learning videos. While for the negative response, learning English using the Google Classroom application is not fun and enough to make students feel bored because students often face obstacles, namely related to poor signal constraints and limited quotas, applications that sometimes have errors and must be updated, limited cellphone storage space makes students have difficulty in downloading the material provided, lack of communication between teachers and students.